2015
DOI: 10.1177/1748048515597872
|View full text |Cite
|
Sign up to set email alerts
|

‘I’d be proud to spend the sacred foreign aid budget on our poor pensioners’: Representations of macro aid resourcing in the Irish, UK and US print-media during the economic crisis, 2008–2011

Abstract: The news-media has been identified as an influence on donor nations' overseas aid allocations, acting as a site where decisions are justified to 'domestic constituencies' and through which resistance is mobilised (Van Belle, 2003). Mediated pressures on aid allocations amplified between 2008 and 2011 in three donor countries experiencing domestic economic difficulties: Ireland, the UK and the US. This study suggests that each country's print-media positioned the macro resourcing of aid primarily as an inward c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This assumption is made on the basis of prior academic research which suggests that parliamentarians base their positions in light of the assumed preferences of their constituents -for example, Baughman (2004) found that parliamentarians with a higher Catholic vote base showed a stronger tendency towards holding socially conservative positions on abortion and sexuality. Therefore, given the above and the persistence of the media campaigning against the 0.7 percent commitment (Cawley, 2015), our constituency marginality hypotheses was as follows:…”
Section: Data Collection and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is made on the basis of prior academic research which suggests that parliamentarians base their positions in light of the assumed preferences of their constituents -for example, Baughman (2004) found that parliamentarians with a higher Catholic vote base showed a stronger tendency towards holding socially conservative positions on abortion and sexuality. Therefore, given the above and the persistence of the media campaigning against the 0.7 percent commitment (Cawley, 2015), our constituency marginality hypotheses was as follows:…”
Section: Data Collection and Hypothesesmentioning
confidence: 99%
“…Between 2010 and 2015 public scepticism about international aid spending being immune from the austerity drive gathered momentum, in part stimulated by a highly sceptical right wing print media (Cawley, 2015). Despite this, Cameron, as the modernising leader of a party that had hitherto not been known for being pro-international aid (Chaney, 2013), persisted in not only ring fencing spending in international aid, but increasing it during a time of widespread public expenditure cuts.…”
Section: Introductionmentioning
confidence: 99%